TWO NEW RECORDS OF CARANGID FISHES FROM INDIAN SEAS - Sreenivasan, P V (Indian Journal of Fisheries, 2011)
Two species of the fishes, belonging to the family Carangidae, Alepes macrurus (Bleeker) and Carangoides coeruleopinnatus (Ruppell) are reported for the fatX time from Indian seas. They are briefly described and their systaniatic positions are discussed